Gerak Tari Kreasi melalui Regio Emilia Approach untuk Meningkatkan Kecerdasan Sosial dan Emosional Anak di Gorontalo - Pupung Puspa Ardini; Milawati Eki (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2019)
The purpose of this research is to know the increase in social intelligence of group B children in the Gorontalo Kindergarten of the Trustees of the City through dance moves creations with the Regio Emilia Approach and find out the increase in emotional intelligence children. The characteristics of the research subjects were children aged 5-6 years. Data collection is carried out by action observation guidelines. The collected data are analyzed statistically using a percentage of several predetermined aspects. The results of this study indicate that (1) in the first cycle, the social intelligence of children from 20 people who completed as many ays 11 people or 55% and those who have not finished are 9 people or 45%, while the aspects of children's emotional intelligence are complete as many as 9 people or 45 % and the unfinished is 11 people or 55%. In the second cycle, the social intelligence of children from 20 people who completed as many as 16 people or 80% and those who have not finished are 4 people or 20%, while in the emotional intelligence aspects of children of 20 people completed as many as 17 people or 85% and those who have not finished are 3 people or 15%. There is an increase in the percentage (%) of the success of the first cycle of cycle II, especially on aspects of child social intelligence from 55% to 80%. The increase occurred by 25% after doing various reflections on learning actions. Whereas in the aspect of emotional intelligence from cycle I to cycle II there was an increase of 30%, from 55% to 85%.